Security education, awareness, and training : from theory to practice - Roper, C. A. (Carl A.) (Elsevier Butterworth-Heinemann, 2006)
This book is the only one available on security training for all level of personnel. Chief Security Officers (CSOs), security managers, and heads of security forces often have to design training programs themselves from scratch or rely on outside vendors and outside training companies to provide training which is often dry, stilted, and not always applicable to a specific corporate or government setting. This title addresses the theories of sound security training and awareness, then shows the reader how to put the theories into practice when developing or presenting any form of security educa.